Postnatal Change in Sulcal Length Asymmetry in Cerebrum of Cynomolgus Monkeys (Macaca fascicularis). Issue 2 (18th December 2013) - Sakamoto, Kazuhito; Sawada, Kazuhiko; Fukunishi, Katsuhiro; Noritaka, Imai; Sakata‐Haga, Hiromi; Yoshihiro, Fukui
ABSTRACT The purpose of this study was to determine the timing of the onset of adult‐type sulcal length asymmetry during postnatal development of the male cynomolgus monkey cerebrum. The monkey brain has already reached adult size by 3 months of age, although the body weight only represents 1/8 of the adult body weight by that time. The fronto‐occipital length and the cerebral width also reached adult levels by that postnatal age with no left/right bias. Consistently, lengths of the major primary sulci reached adult levels by 3 months of age, and then decreased slightly in sexually mature monkeys (4–6.5 years of age). Asymmetry quotient analysis showed that sulcal length asymmetry patterns gradually changed during postnatal development. The male adult pattern of sulcal length asymmetry was acquired after 24 months of age. In particular, age‐dependent rightward lateralization of the arcuate sulcal length was revealed during cerebral maturation by three‐way ANOVA. The results suggest that the regional difference in cerebral maturation from adolescence to young adulthood modifies the sulcal morphology with characteristic asymmetric patterns in male cynomolgus monkeys. Anat Rec, 297:200–207, 2014. © 2013 Wiley Periodicals, Inc.